Longitudinal study on the effect of keratinized mucosal augmentation surrounding dental implants in preventing peri-implant bone loss - Takeshi Kikuchi; Masahiro Wada; Tomoaki Mameno; Daisuke Hasegawa; Giovanni Serino; Kazunori Ikebe (PeerJ, 2022)
Background Dental implant therapy is a well-established method of prosthetic rehabilitation of missing teeth. To maintain the health of the surrounding tissue, management of risk factors/indicators and daily maintenance are important. It still remains controversial whether a certain amount of keratinized mucosal width is essential for maintaining the health of peri-implant tissue. The purpose of this multicenter retrospective study was to assess the correlation between bone loss around dental implant and the amount of keratinized tissue width. Methods A total of 1,644 implants were evaluated. Data was collected about participants’ general and dental history, as well as implant details. Bone resorption around implant was calculated from intra-oral radiographs taken after 1 year and more than 3 years of function. Implants were classified into three groups; received free gingival graft or apically repositioned flap surgery for increasing the keratinized mucosa ≥2 mm width (group A), keratinized mucosa width ≥2 mm (group B), and keratinized mucosa width <2 mm (group C). These data were analyzed by propensity score analysis and a generalized linear regression analysis was performed to compare the bone resorption among groups. Results Mean functional time was 55.8 months (SD = 20.5) in group A, 67.6 months (SD = 28.1) in group B, and 74.5 months (SD = 32.9) in group C. Mean bone resorption of groups A, B, and C were 0.08 mm (SD = 0.40), 0.18 mm (SD = 0.66), and 0.44 mm (SD = 0.40). Groups A and B had significantly lower bone resorption than group C. Conclusion The results in this study show the importance of keratinized mucosa in maintaining the peri-implant bone. Our findings also suggest that mucosal transplantation is useful, as opposed to narrowing of the keratinized mucosa.